Cognitive and Emotional Engagement in Stoichiometry Learning: A Correlational Study - Waviza; Erlina; Eni Mayasari (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The purpose of this study was to measure the strength of the relationship between students’ cognitive and emotional engagement in stoichiometry learning. This research employed a descriptive quantitative approach, including descriptive analysis and correlational analysis. The participants consisted of 70 eleventh-grade students enrolled in the science-track chemistry course, drawn from two classes: Grade XI Chemistry 1 and Grade XI Chemistry 2. Data were collected using a four-point Likert-scale questionnaire measuring cognitive and emotional engagement, as well as through observations, semi-structured interviews, and documentation. The results showed that: (1) students’ cognitive engagement was categorized as very high (13%), high (34%), low (43%), and very low (10%); (2) students’ emotional engagement was categorized as very high (20%), high (16%), low (53%), and very low (11%); (3) the correlation test between cognitive and emotional engagement was significant (0.000 < 0.05), indicating a positive relationship; and (4) the strength of the relationship between cognitive and emotional engagement, as indicated by Spearman’s rho, was 0.447, which represents a moderate level of correlation. Therefor, higher cognitive engagement is associated with higher emotional engagement, and vice versa.